Discussions on design of precast prestressed planks and biaxially-loaded slender columns using EN 1992-1-1:2004 - Tan, Kang Hai (2013)
The first part of the paper presents a comparison of prestressed plank design at serviceability limit state between BS 8110 and EN 1992-1-1:2004 (EC2). While for the ultimate limit state design there is no considerable gap in the results, there is a significant change in design at the serviceability limit state. An example is given to demonstrate the comparison. In the second part, structural responses and failure loads obtained from a test series on reinforced concrete slender columns subjected to biaxial bending are compared to those determined from the design methods based on nominal stiffness and nominal curvature in accordance with EC2. BS, ACI, finite element-based and analytical analyses are also incorporated into the discussion. Both the EC2 methods provide better agreement with the test results compared to the other methods. Besides, more conservative predictions are obtained from the EC2 method of nominal curvature.